A Meta-Analysis on Vitamin D Supplementation and Asthma Treatment - Liu, Meiqi; Wang, Jun; Sun, Xinrong (Frontiers in Nutrition, 2022)
Background Vitamin D, as an immunomodulator, may be related to the therapeutic effect of asthma patients, but the research in this area is still controversial. The aim of this meta-analysis was to analyze the role of vitamin D supplementation in the treatment of asthma patients. Methods Randomized Controlled Trials (RCTs) of vitamin D supplementation in asthma were searched in PubMed, EMBASE, and the Cochrane library. Primary outcomes were forced expiratory volume in one second (FEV1), asthma exacerbations, Asthma Control Test scores (ACT scores), and fractional exhaled nitric oxide (FENO). Results A total of 10 RCTs were included, including 1349 patients. Vitamin D supplementation didn’t affect the ACT scores (SMD 0.04, 95%CI -0.13 to 0.21, P=0.87), FEV1 (SMD 0.04, 95%CI -0.35 to 0.43, P<0.01) and FENO (SMD -0.01, 95%CI -0.22 to 0.20, P=0.27), but reduced the rate of asthma exacerbations (RR 0.69, 95%CI 0.41 to 0.88, P<0.01), especially in subgroups of children (RR 0.46, 95%CI 0.30 to 0.70, P=0.83) and follow up time less than 6 months (RR 0.45, 95%CI 0.32 to 0.63, P=0.95). Additionally, though there was only one study included in the subgroup, it significantly enhanced FEV1 at the last visit for patients whose FEV1 baseline value was less than 70% (SMD 0.94, 95%CI 0.47 to 1.41). Conclusion Vitamin D supplementation can reduce asthma exacerbations, especially in children, and within 6 months of follow up time. In addition, vitamin D has a positive effect on improving FEV1 of patients whose FEV1 baseline value is less than 70%, but more RCTs are still needed to support this conclusion.